Temperature coefficients of Li-ion battery single electrode potentials and related entropy changes – revisited. Issue 4 (14th January 2019) - Swiderska-Mocek, A.; Rudnicka, E.; Lewandowski, A.
Abstract : Here, single electrode potential temperature coefficients were estimated using negligible thermal diffusion potential assumption. Abstract : Usually the potentials of Li-ion battery electrodes (at constant temperature) are expressed against metallic lithium, assuming that it equals zero. In the case of potential temperature coefficients, and hence entropies, no similar assumption can be applied, as it is against the third principle of thermodynamics. Here, single electrode potential temperature coefficients were estimated using a 'negligible thermal diffusion potential assumption'. The open circuit voltage (Δ ϕ i ) dependence on temperature T, for three Li-ion battery cathodes, was measured in non-isothermal symmetrical cells (both electrodes had the same composition but were kept in different temperatures). The measured values were interpreted as single cathode (LiMn2 O4, LiFePO4 and LiCoO2 ) potential temperature coefficients d ϕ i /d T, assuming that Soret and Thomson effects are negligible. The single cathode potential temperature coefficients, estimated in such a way, were positive (d ϕ (LiMn2 O4 )/d T = 0.86 mV K −1, d ϕ (LiFePO4 )/d T = 0.86 mV K −1 and d ϕ (LiCoO2 )/d T = 0.83 mV K −1 ). In addition to the measurements in non-isothermal cells, the temperature coefficients of the open circuit voltage of isothermal cells consisting of these cathodes and a metallic lithium reference (d E /d T ) were determined. In this case, all temperature coefficients of the cell voltage were negative (d E (Li|LiMn2 O4 )/d T = −0.20 mV K −1, d E (Li|LiFePO4 )/d T = −0.08 mV K −1 and d E (Li|LiCoO2 )/d T = −0.25 mV K −1 ). The temperature coefficient of the single metallic-lithium electrode, d ϕ Li /d T, was calculated from the temperature coefficients d E /d T of isothermal cells consisting of the cathodes and a lithium counter-electrode and the d ϕ i /d T values measured in non-isothermal cells: d E /d T = d ϕ i /d T − d ϕ Li /d T . The d ϕ Li /d T value was 1.03 mV K −1 . The measured difference in the d ϕ /d T values for metallic lithium and graphite (LiC6 ) anodes was small (d E /d T = d ϕ (C6 Li)/d T − d ϕ Li /d T = −0.08 mV K −1 ). Literature data on the temperature coefficients of the isothermal cell open circuit voltage containing different electrodes at different states of charge (SOC) and metallic-lithium counter electrodes were used for the calculation of single electrode properties, taking into account that d ϕ Li /d T = 1.03 mV K −1 . The temperature coefficients of all single electrodes were positive for different SOC values and ranged between 1.69 mV K −1 and 0.84 mV K −1 . The values of entropy change, Δ S i, for reversible single electrode reactions were all positive (for different states of charge) and ranged between ca. 70 J mol −1 K −1 and 120 J mol −1 K −1 .